Editorial - Van Patten, Elia María (1980)
We have been very active this last month, laying off librarians and receiving others. We visit this semester in the program OEA/ UNA / MEP/, eight and 36 Nicaraguan Central Library. We have initiated a training program using audiovisual which gives comprehensive information on this issue.